The rule of an empire: Megiddo in the Late Bronze Age - Martin, Mario A. S.; Finḳelshṭayn, Yiśraʾel (Near Eastern archaeology, 2025)
During the Egyptian empire in the Late Bronze Age Megiddo was the hub of a city-state linked to all areas of the eastern Mediterranean, and its fate was determined by the macro-political events of the time. Early in the period, especially in the aftermath of the Battle of Megiddo in 1457 BCE, the city was in decline. A long spell of revival and prosperity ensued in the fourteenth (Amarna Age) and thirteenth centuries. The twelfth century brought a period of crisis, which caused the downfall of the Late Bronze city in several steps; various quarters were hit at different times and intensity. The final blow is marked by the fiery destruction of the palace district in the early eleventh century, more than a generation after the demise of the Egyptian empire.